Examining the Causes and Prevention of Book Losses in Academic Libraries - Abid Hussain, Muhammad Ibrahim (IJoLIS, 2024)
Purpose: This article is an attempt to exAMine the current situation of book losses/theft, their causes, and remedies that have been taken by academic libraries in Pakistan